Why the process is so Important for a DIRFloortime specialist - I.V. Naidina (Moscow State University of Psychology and Education, 2019)
DIRFloortime® is a learning approach tailored to individual characteristics of the adult and child and based on establishing emotionally charged relationships, which is successfully used to help children with autistic spectrum disorders. An expert trained in DIRFloortime® offers her thoughts on the importance of the interaction process between children and adults during sessions and in the real-life setting. The paper reviews following the child's lead and challenging - the main strategies of the DIRFloortime approach. It describes the concept of the circle of communication and characteristics of the interaction process, such as tempo, rhythm, duration, intensity, and content. The process of interaction with children affected by autistic spectrum disorder who have difficulties in communicating should be arranged so that they can be engaged and remain in this process with pleasure and joy as long as possible. The child must feel successful and valuable in the eyes of adults who help him/her grow up. Then the child will be able to cope with his fears, shyness, perceptual and motor challenges and to grow in a most harmonious way. This is why DIRFloortime creators and therapists give particular importance to the process of interaction.